Effectiveness of the translation of puns as subtitles in conveying wit and humour - Lau, Tsin Ning (2015)
Subtitle translation is a relatively new field and much has been done with respect to the translation of puns in other media. However there is a lack of research done with regards subtitle translation of puns from English to Chinese. This paper will focus on investigating the effectiveness of the subtitle translation of puns in conveying wit and humour using a quantitative method, including questionnaires with an open-ended component. The puns used fall into three categories—single-meaning puns, double-meaning puns and spoonerisms according to Lederer (1981). Literature reviewed suggests double-meaning puns to be the most effective in conveying wit and humour in advertising and stand-up comedy, but results are inconclusive. 35 18 to 26 years olds participated in the study and results prove that Version 2 subtitles, constructed with a source text pun to target text pun strategy, used commonly for the translation of puns, is more effective in conveying wit and humour than Version 1 subtitles which use the general strategy for subtitle translation of source text pun to target text literally translated pun. This indicates that most participants were still able to understand the perlocutionary effect of Version 2 subtitles despite constraints faced in subtitle translation.